Combinatorial targeting of early pathways profoundly inhibits neurodegeneration in a mouse model of glaucoma - Gareth R. Howell; Katharine H. MacNicoll; Catherine E. Braine; Ileana Soto; Danilo G. Macalinao; Gregory L. Sousa; Simon W.M. John (Neurobiology of Disease, 2014)
The endothelin system is implicated in various human and animal glaucomas. Targeting the endothelin system has great promise as a treatment for human glaucoma, but the cell types involved and the exact mechanisms of action are not clearly elucidated. Here, we report a detailed characterization of the endothelin system in specific cell types of the optic nerve head (ONH) during glaucoma in DBA/2J mice. First, we show that key components of the endothelin system are expressed in multiple cell types. We discover that endothelin 2 (EDN2) is expressed in astrocytes as well as microglia/monocytes in the ONH. The endothelin receptor type A (Ednra) is expressed in vascular endothelial cells, while the endothelin receptor type B (Ednrb) receptor is expressed in ONH astrocytes. Second, we show that Macitentan treatment protects from glaucoma. Macitentan is a novel, orally administered, dual endothelin receptor antagonist with greater affinity, efficacy and safety than previous antagonists. Finally, we test the combinatorial effect of targeting both the endothelin and complement systems as a treatment for glaucoma. Similar to endothelin, the complement system is implicated in a variety of human and animal glaucomas, and has great promise as a treatment target. We discovered that combined targeting of the endothelin (Bosentan) and complement (C1qa mutation) systems is profoundly protective. Remarkably, 80% of DBA/2J eyes subjected to this combined inhibition developed no detectable glaucoma. This opens an exciting new avenue for neuroprotection in glaucoma.